2016
DOI: 10.1002/aic.15533
|View full text |Cite
|
Sign up to set email alerts
|

On near‐wall jets in a disc‐like gas vortex unit

Abstract: in Wiley Online Library (wileyonlinelibrary.com) To clarify the three-dimensional (3D) structure of near-wall jets observed in disc-like gas vortex units (GVUs), experimental and numerical studies are performed. The experimental results are obtained using stereoscopic particle image velocimetry (PIV), laser doppler anemometry, pressure probes and surface oil flow visualization techniques. The first three techniques have been used to investigate the bulk flow hydrodynamics of the vortex unit. Surface oil flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 25 publications
(39 reference statements)
1
20
0
Order By: Relevance
“…A smaller slot angle also results in the presence of smaller (or no) jets (and consequently, smaller counterflow region) in the unit, which subsequently reduces or eliminates the counterflow region. A detailed computational analysis of this phenomenon has already been by provided by Niyogi et al Less inclined inlet slots give smaller intensity jets. The smaller the counterflow region, the faster it disappears.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A smaller slot angle also results in the presence of smaller (or no) jets (and consequently, smaller counterflow region) in the unit, which subsequently reduces or eliminates the counterflow region. A detailed computational analysis of this phenomenon has already been by provided by Niyogi et al Less inclined inlet slots give smaller intensity jets. The smaller the counterflow region, the faster it disappears.…”
Section: Resultsmentioning
confidence: 99%
“…Swirl decay due to the exhaust wall friction generates an adverse pressure gradient along the exhaust line resulting in an extended backflow. The latter is discussed in more detail by Niyogi et al…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…The axisymmetric assumption is considered valid, based on previous work, where it was shown that the use of multiple equidistant injection slots (36) uniformly distributes the gas in the GVU and makes the flow nearly axisymmetric even in the vicinity of the injection slots. 29 The no-slip boundary condition is imposed at the end-walls of the GVU. The Reynolds Averaged Navier-Stokes (RANS) turbulence modeling approach is adopted, as the main goal of the present work is to obtain ensemble-averaged GVU hydrodynamics.…”
Section: Numerical Modelmentioning
confidence: 99%